Role of Helicobacter pylori Eradication Therapy on Platelet Recovery in Chronic Immune Thrombocytopenic Purpura - Khan Sheema; Ujjan Ikramdin; Naz Arshi; Naz Farah; Sheikh Imran (Gastroenterology Research and Practice)
Background. Idiopathic thrombocytopenic purpura (ITP) is a bleeding disorder in which the immune system destroys native platelets. In this condition an autoantibody is generated against a platelet antigen. ITP affects women more often than men and is more common in children than adults. Objective. To assess the effect of Helicobacter pylori eradication therapy (HPET) on platelet count in Helicobacter pylori associated chronic immune thrombocytopenic purpura (chronic ITP) in adult. Materials and Methods. It is an interventional prospective study conducted at Liaquat University of Medical and Health Sciences, Jamshoro, from 2014 to 2015. A set of 85 patients diagnosed with chronic ITP were included in the study via convenient sampling. Patients with platelets count < 100 × 109/L for >3 months were selected. They were posed to first-line investigations which comprised complete blood count (CBC) and peripheral blood smear examination followed by second-line tests including bone marrow examination and Helicobacter pylori stool specific antigen (HpSA-EIA). Standard H. pylori eradication therapy was offered and the patients were assessed at regular intervals for 6 months. Results. Of the 85 study patients, 32 (37.6%) were male and 53 (62.3%) were female. Mean ages of H. pylori positive and negative subjects were 43.89 ± 7.06 and 44.75 ± 7.91 years, respectively. Bone marrow examination confirmed the diagnosis and excluded other related BM disorders. H. pylori stool antigen (HpSA) was detected in 34 (40%) patients and hence regarded as H. pylori positive; the rest were negative. Treatment with eradication therapy significantly improved the mean platelet counts from 48.56±21.7 × 109/l to 94.2±26.8 × 109/l. Conclusion. We concluded that the anti-H. pylori eradication therapy improves blood platelet counts in chronic immune thrombocytopenia.